2019
DOI: 10.7554/elife.39694
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of motor-mediated microtubule streaming

Abstract: We introduce a filament-based simulation model for coarse-grained, effective motor-mediated interaction between microtubule pairs to study the time-scales that compose cytoplasmic streaming. We characterise microtubule dynamics in two-dimensional systems by chronologically arranging five distinct processes of varying duration that make up streaming, from microtubule pairs to collective dynamics. The structures found were polarity sorted due to the propulsion of antialigned microtubules. This also gave rise to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…A similar opinion was proposed that self-propelled objects, such as gilding MTs, show progressively larger probabilities to align with their neighbors [ 66 ]. Recently, an important supplement to these hypotheses stated that MTs align and are actively transferred from their original bundle to another anti-aligned bundle [ 67 ]. All the theories indicated that alignment is a critical step in the formation of collective motion, and the formation of MT bundles is a dynamic process.…”
Section: Resultsmentioning
confidence: 99%
“…A similar opinion was proposed that self-propelled objects, such as gilding MTs, show progressively larger probabilities to align with their neighbors [ 66 ]. Recently, an important supplement to these hypotheses stated that MTs align and are actively transferred from their original bundle to another anti-aligned bundle [ 67 ]. All the theories indicated that alignment is a critical step in the formation of collective motion, and the formation of MT bundles is a dynamic process.…”
Section: Resultsmentioning
confidence: 99%
“…3; note the y axis log scale). 14,23,[39][40][41][42][43][44][45][46][47][48] Interestingly, the exponentially decaying tails appear to be there also for shorter timescales (Fig. S4, ESI †), though the statistics is necessarily poorer.…”
Section: Resultsmentioning
confidence: 99%
“…13 Moreover, microfilaments, which are regarded as thin and long polymer chains, show a tread-milling motion in the ATP solution 14 or associate with motor proteins. [15][16][17] To understand how an active force governs the non-equilibrium dynamics of biopolymers, an active polymer model has been proposed recently, 18,19 where a self-propulsion force is imposed tangentially on the polymer. The active polymer displays a rich phenomenology 20,21 such as super-diffusion, rotational motion, helical motion, 22,23 and collective motion.…”
Section: Introductionmentioning
confidence: 99%